Critical insights into the effect of shear on in situ reduction of graphene oxide in PVDF: assessing by rheo-dielectric measurements. (20th May 2016) - Sharma, Maya; Madras, Giridhar; Bose, Suryasarathi
Abstract: In situ reduction of graphene oxide (GO) during the preparation of conducting polymeric nanocomposites has been explored recently. In this study, the in situ reduction of GO in poly (vinylidene fluoride) (PVDF) under different conditions like quiescent, high and low shear, pre-shear has been investigated in detail. To accomplish this, PVDF/GO composites were prepared by both melt and solution blending. The bulk electrical conductivity of melt mixed composites, which had undergone extensive shear during preparation, was monitored by a rheo-dielectric setup and compared with the composites which experienced low shear. In addition, the bulk electric conductivity was also measured in situ for the composites that had undergone quiescent compositing. Comprehensive characterization of the composites reveals that GO is in situ reducing under all processes but the improvement in conductivity is dependent on the adopted process. Compression molded samples, which were annealed for 45 min, showed highest melt conductivity among all the adopted processes. The intense shearing of composites at high temperature in melt extrusion led to re-stacking of graphene sheets and resulted in decreased bulk electrical conductivity. Surprisingly, melt conductivity decreases with shear and time in all composites. This study can help in understanding the reduction of GO during intense shearing of composites.